Effect of Online Review on Product Sales: Study on Shopee Mall Fashion Brand - Nurkholish Majid; Virginia Mandasari (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2022)
The development of the internet massively affects business sector, including e-commerce. The advancement of e-commerce has given rise to a marketplace where sellers and buyers meet online, one of which is Shopee. This study aims to analyze the effect of online reviews with rating attributes, comments and photos on product sales at Shopee Mall. The sample consists of 200 brands/stores registered at Shopee Mall. Secondary data obtained from ratings, comments, photos and sales of each brand/store at Shopee Mall was analyze using multiple regression. The results showed that online reviews and their attributes, namely ratings, comments and photos, had an influence and were able to increase sales of fashion products at Shopee Mall.